Comparison of long-term safety and efficacy outcomes after drug-eluting and bare-metal stent use across racial groups: Insights from NHLBI Dynamic Registry. (1st April 2015) - Olafiranye, Oladipupo; Vlachos, Helen; Mulukutla, Suresh R.; Marroquin, Oscar C.; Selzer, Faith; Kelsey, Sheryl F.; Williams, David O.; Strollo, Patrick J.; Reis, Steven E.; Lee, Joon S.; Smith, A.J. Conrad
Abstract: Background: Long-term data on outcomes after percutaneous coronary intervention (PCI) with drug-eluting stent (DES) and bare-metal stent (BMS) across racial groups are limited, and minorities are under-represented in existing clinical trials. Whether DES has better long-term clinical outcomes compared to BMS across racial groups remains to be established. Accordingly, we assessed whether longer-term clinical outcomes are better with DES compared to BMS across racial groups. Methods: Using the multicenter National Heart, Lung, and Blood Institute (NHLBI)-sponsored Dynamic Registry, 2-year safety (death, MI) and efficacy (repeat revascularization) outcomes of 3326 patients who underwent PCI with DES versus BMS were evaluated. Results: With propensity-score adjusted analysis, the use of DES, compared to BMS, was associated with a lower risk for death or MI at 2 years for both blacks (adjusted Hazard Ratio (aHR) = 0.41, 95% CI 0.25–0.69, p < 0.001) and whites (aHR = 0.67, 95% CI 0.51–0.90, p = 0.007). DES use was associated with a significant 24% lower risk of repeat revascularization in whites (aHR = 0.76, 95% CI 0.60–0.97, p = 0.03) and with nominal 34% lower risk in blacks (aHR = 0.66, 95% CI 0.39–1.13, p = 0.13). Conclusion: The use of DES in PCI was associated with better long-term safety outcomes across racial groups. Compared to BMS, DES was more effective in reducing repeat revascularization in whites and blacks, but this benefit was attenuated after statistical adjustment in blacks. These findings indicate that DES is superior to BMS in all patients regardless of race. Further studies are needed to determine long-term outcomes across racial groups with newer generation stents. Highlights: Use of DES in PCI was associated with lower rates of death or MI in blacks and whites in the NHLBI Registry at 2 years. DES use was also associated with lower rate of repeat revascularization in blacks and whites. Benefit of DES on repeat revascularization remained significant in whites but attenuated in blacks after adjustment.